Diversity in Mosses of Pithoragarh and its Neighbouring Areas, Western Himalaya, India - Sahu, Vinay; Asthana, A. K. (Indian Forester, 2015)
Present study provides an account of 72 taxa of mosses belonging to 24 families. During the study five mosses Fissidens polysetulus C. Muell. ex Gangulee & Norkett, Ectropothecium kerstanii Dix. & Herz., Isopterygium serrulatum Fleisch., Weissia edentula Mitt., Rhachithecium perpusillum (Thwait & Mitt.) Broth. are new to western Himalaya, while 10 mosses are new to Kumaon Himalaya.